Circle soccer training. 100 games and drills to improve game competence - Kerber, S.; Seeger, F. (Meyer & Meyer Sport (UK) Ltd., 2019)
Training players in circular playing fields develops and improves their game competence. Circle Soccer Training contains an integrated game concept and provides varied training exercises for fast implementation in training practice that will benefit all players at any level. The book first delves into the theory of circle training, explaining the main technical and tactical principles of the circle training concept. It contains further helpful information regarding the rules of the game, coaching points, how to organize each game or drill, and detailed illustrations. Following the introduction on circle training is the practical application. Beginning with an explanation on how to use this effective training for improving players` technical abilities, this section contains 100 circular games and drills that will allow players to progress and develop their skills. Also presented in this book are trendy, innovative, and cognitively demanding forms of play, which are an integral and complex part of modern soccer. The concepts of circle soccer and their application in training are important for all players—at any level—to develop their technical playing abilities. With Circle Soccer Training, players can create a competitive advantage over their opponents. Klappentext